2008
DOI: 10.1007/s11295-007-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of an STS map of an interspecific progeny of Malus

Abstract: Simple sequence repeat (SSR) markers developed from Malus, as well as Prunus, Pyrus and Sorbus, and some other sequence-tagged site (STS) loci were analysed in an interspecific F 1 apple progeny from the cross 'Fiesta' × 'Totem' that segregated for several agronomic characters. A linkage map was constructed using 259 STS loci (247 SSRs, four SCARs and eight known-function genes) and five genes for agronomic traits-scab resistance (Vf), mildew resistance (Pl-2), columnar growth habit (Co), red tissues (Rt) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 55 publications
1
29
1
Order By: Relevance
“…"Totem" (F × T; Fernández-Fernández et al 2008), the diploid Fragaria reference bin mapping population (N=6) Fragaria vesca 815 × Fragaria nubicola 601 F 2 (FV × FN; Sargent et al 2008), and the Prunus reference bin mapping population (N=6) Prunus dulcis "Texas" × P. persica "Earlygold" F 2 (T × E; Howad et al 2005). An additional diploid Fragaria population-the 815×903BC population (N=93) of Nier et al (2006)was used to confirm the map position of one marker where the segregation scores produced using the FV × FN bin set were ambiguous.…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…"Totem" (F × T; Fernández-Fernández et al 2008), the diploid Fragaria reference bin mapping population (N=6) Fragaria vesca 815 × Fragaria nubicola 601 F 2 (FV × FN; Sargent et al 2008), and the Prunus reference bin mapping population (N=6) Prunus dulcis "Texas" × P. persica "Earlygold" F 2 (T × E; Howad et al 2005). An additional diploid Fragaria population-the 815×903BC population (N=93) of Nier et al (2006)was used to confirm the map position of one marker where the segregation scores produced using the FV × FN bin set were ambiguous.…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 99%
“…Alleles at segregating loci in the F × T mapping population were coded for analysis using JoinMap 4.0 and incorporated into the dataset of Fernández-Fernández et al (2008) as follows. Genetic distances were calculated using regression mapping applying the Kosambi mapping function and marker positions were determined using a recombination fraction threshold of 0.35, ripple value of 1.0, jump threshold of 3.0, and triplet threshold of 5.0.…”
Section: Segregation Data Analysis and Marker Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, three nearly identical R2R3 MYB transcription factors (MdMYBA,MdMYB1 and MdMYB10) were shown to be involved in the regulation of red coloration in apple (Takos et al 2006;Ban et al 2007;Espley et al 2007). Genetically it was shown that the red pigmentation of Xesh and foliage can be determined by a unique single locus Rni (R for red and ni for niedzwetzkyana) on linkage group 9 of apple, which co-segregates with MdMYB10 (Chagné et al 2007;Fernández-Fernádez et al 2008). The MdMYBA gene was also mapped at the same region on LG9 in a population 'Delicious' £ 'Mitsubakaido' (Ban et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Silfverberg-Dilworth et al (2006) constructed a map, which is currently used as reference map, by adding a new set of SSR markers to the previous linkage map. A new map including several major genes and summarizing the position of 247 SSR was also recently published by Fernandez-Fernandez et al (2008).…”
Section: Introductionmentioning
confidence: 99%